2001
DOI: 10.1111/j.1574-6968.2001.tb10758.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and genotypic characterization by PFGE of clinical and environmental isolates of enterococci

Abstract: Fifty-four Enterococcus faecalis and 20 Enterococcus faecium isolates from clinical and non-human sources in Rome, Italy, were characterized by antibiotic resistance and pulsed field gel electrophoresis (PFGE). Resistance to vancomycin, teicoplanin, ampicillin, and ciprofloxacin was more frequent in E. faecium than in E. faecalis, whereas high-level resistance to aminoglycoside was found primarily in E. faecalis. Multi-resistance was found primarily among clinical isolates, but was also observed among environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…The use of molecular methods such as AFLP and PFGE has led to major advancements in the understanding of the epide- (3,8,30), and from hospital outbreaks (14,19,21,24). However, these methods often have proven too discriminatory to establish genetic relationships in a broader setting and to gain general insight about isolates from diverse areas and typed by different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular methods such as AFLP and PFGE has led to major advancements in the understanding of the epide- (3,8,30), and from hospital outbreaks (14,19,21,24). However, these methods often have proven too discriminatory to establish genetic relationships in a broader setting and to gain general insight about isolates from diverse areas and typed by different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increases of MAR (multiple-antibiotic-resistant) bacteria observed in various aquatic systems may be of significant importance of health since human infections caused by such organisms could be difficult to treat with drugs (Chandrasekaran, Venkatesh, Lalithakumari, 1998;De Vicente, Avilés, Codina, Borrego, & Romero, 1990;Dicuonzo et al, 2001;Lopes et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Their ability to survive in different environmental conditions, innate resistance to many antibiotics, and ability to acquire, accumulate, and transfer genetic determinants of resistance are reasons for their increased significance as human and animal pathogens (6,18,22,24,27). Many authors have indicated a possible transfer of the resistant enterococci from animals to humans via the food chain; however, opinions on this matter are divided (1,3,4,10,12,14,15,(18)(19)(20)(21)(22)(23)25). In Poland, there are no available data about the antimicrobial resistance of enterococci isolated from meat; therefore, the aim of the study was the evaluation of this phenotypic feature among strains of Enterococcus faecalis.…”
Section: Introductionmentioning
confidence: 99%